The Influence of Service Quality of Mobile Phone on Customer Satisfaction in Malaysia: A Students’ Feedback Survey (Journal of Business Management and Accounting, 2011)
The study examines the student’s satisfaction of the quality of services rendered by mobile phone service provider in Malaysia. A cross-sectional survey was conducted using 342 postgraduate students of Universiti Utara Malaysia main campus at Sintok. The result reveals that tangibility was the most important dimension of mobile service quality, while empathy was found to be the least important dimension. The result further shows that the adjusted R² of 0.435 indicates 43.5 percent of variance in customer satisfaction could be predicted by the quality of service delivered by the mobile service providers. Based on the fi ndings, it is therefore recommended that the mobile service providers could make some paradigm changes with regard to the fi ve dimensions of service quality in order to enhance customers’ satisfaction. These changes include focusing on tangible cues, fulfi lling promises, being courteous all of which customers used to evaluate service delivery. Finally, limitations of the study were highlighted, and consequently directions for future research were suggested.